International migration and policy: Xenophobia in structure of immigration policy of US, UK and South Africa - Ekwonna, Sampson I. (SOUTH EAST JOURNAL OF POLITICAL SCIENCE, 2021)
The continued attack on the lives and property of foreigners --- especially, Nigerians --- in South Africa of the recent times and the very deafening silence of its political leadership in the face of a clear affront on its law-and-order leave a worrying feeling of either (a complete) lawlessness or a certain pattern to the madness. Since there is not much supporting evidence of a general war of all on all, we are wont to support the latter. Our intent is to investigate the now trending xenophobic attacks to fully understand its meaning, manifestation, implications in international law among civilized nations, and its prevalence among states. This paper adopts a descriptive research design and its method of analysis is cross country comparative, using secondary data drawn from existing literature. For explanation, we are going to rely on the national identity approach.